Ferromagnetic-antiferromagnetic Competition in Diluted Magnetic Semiconductors - Huu Nha, Nguyen; Van Nham, Phan (VNU Journal of Science: Mathematics - Physics, 2022)
The signature of the magnetic competition in a nearly filled impurity band diluted magnetic semiconductors is addressed. In the formalism of the Kondo lattice model, self-consistent equations determining the Green function of the itinerant carrier in the system are evaluated by use of the dynamical mean-field theory. An analytical solution of the static spin susceptibility of the itinerant carrier to specify the magnetic instability is then established. Once the impurity band is nearly filled, one finds the antiferromagnetic instability against the ferromagnetic state. Phase diagrams of the magnetic structures in the diluted magnetic semiconductor were also discussed.